Improved 2000-m rowing performance in a cool environment with an external heating garment - Cowper, G.; Barwood, M.; Goodall, S. (International Journal of Sports Physiology and Performance, 2021)
Purpose: Rowers can be in marshaling areas for up to 20 to 25 min before the start of a race, which likely negates any benefits of an active warm-up, especially in cold environments. It is unknown if using a heated jacket following a standardized rowing warm-up can improve 2000-m rowing performance. Methods: On 2 separate occasions, 10 trained male rowers completed a standardized rowing warm-up, followed by 25 min of passive rest before a 2000-m rowing time trial on a rowing ergometer. Throughout the passive rest, the participants wore either a standardized tracksuit top (CON) or an externally heated jacket (HEAT). The trials, presented in a randomized crossover fashion, were performed in a controlled environment (temperature 8°C, humidity 50%). Rowing time-trial performance, core body temperature, and mean skin temperature, along with perceptual variables, were measured. Results: During the 25-min period, core body temperature increased in HEAT and decreased in CON (?0.54°C [0.74°C] vs -0.93°C [1.14°C]; P = .02). Additionally, mean skin temperature (30.22°C [1.03°C] vs 28.86°C [1.07°C]) was higher in HEAT versus CON (P < .01). In line with the physiological data, the perceptual data confirmed that participants were more comfortable in HEAT versus CON, and subsequently, rowing performance was improved in HEAT compared with CON (433.1 [12.7] s vs 437.9 [14.4] s, P < .01). Conclusion: The data demonstrate that an upper-body external heating garment worn following a warm-up can improve rowing performance in a cool environment.